2006
DOI: 10.1088/0268-1242/22/2/017
|View full text |Cite
|
Sign up to set email alerts
|

A room temperature, or moderately cooled, fast THz semiconductor hot electron bolometer

Abstract: A fast THz bolometer is proposed in which, unlike the conventional thermal one, electromagnetic radiation heats only electrons in a narrow gap semiconductor without its lattice inertial heating. Under determined conditions, this heating changes generation-recombination processes that cause the carrier number to decrease and the semiconductor resistance to rise. The Hg 0.8 Cd 0.2 Te detector noise equivalent power in the range of 77-300 K can reach ∼10 −11 W for frequencies of about 1 THz and signal gain freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…6 the value S V = ÄV/W rad~0 .3 V/W, and the NEP, calculated as NEP = U noise /S V at Df = 1 Hz, equals NEP~2.5×10 -9 W (U noise is taken from the above noise theoretical estimations). At y » 0 o , the measured sensitivity was S V~2 V/W and the estimated NEP~3.5×10 -10 W at Df = 1 Hz, the same as for n = 0.89 THz band [16]. These both values (S V and NEP) substantially differ from the estimated theoretical ones, in which the contact antenna coupling was not taken into account: S Vtheor = 4.2 mV/W and NEP theor = 1.7×10 -7 W. As the source of THz radiation (l = 337 µm), the sputter-ion hollow-cathode HCN laser was used [23].…”
Section: Experiments and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…6 the value S V = ÄV/W rad~0 .3 V/W, and the NEP, calculated as NEP = U noise /S V at Df = 1 Hz, equals NEP~2.5×10 -9 W (U noise is taken from the above noise theoretical estimations). At y » 0 o , the measured sensitivity was S V~2 V/W and the estimated NEP~3.5×10 -10 W at Df = 1 Hz, the same as for n = 0.89 THz band [16]. These both values (S V and NEP) substantially differ from the estimated theoretical ones, in which the contact antenna coupling was not taken into account: S Vtheor = 4.2 mV/W and NEP theor = 1.7×10 -7 W. As the source of THz radiation (l = 337 µm), the sputter-ion hollow-cathode HCN laser was used [23].…”
Section: Experiments and Discussionmentioning
confidence: 67%
“…Some preliminary considerations and experimental data for the wavelengths l = 8 mm and l = 337 µm were shortly presented earlier [16]. The device operation takes into account the phenomena in semiconductor bipolar plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these structures are of interest for the creation of semiconductor THz detectors based on hot electrons operating under moderate cooling (up to liquid nitrogen temperature) or ambient temperatures. It is known that narrow gap semiconductors are promising materials for direct THz detectors due to high electron mobility, high carrier concentration and low effective masses of electrons [3,43]. In our case, we should expect the electron relaxation time of about 10 -11 s and scattering mean free path of about 50 μm.…”
Section: Results For Electron Mobility In Cdte/hg 1-x CD X Te/cdte Qumentioning
confidence: 72%
“…The radiation can enter and through the de− tector surface x = 0 too. For the latter case, a bolometer model is developed in article [9]. Its comparison with expe− riment has shown that even a primitive antenna allows us to enter the radiation energy flow much greater than the above detector surface itself does it.…”
Section: Bolometer Design Model Principal Assumptions and Basic Equmentioning
confidence: 99%